An RNA Aptamer Targeting the Receptor Tyrosine Kinase PDGFRα Induces Anti-tumor Effects through STAT3 and p53 in Glioblastoma - Sorah Yoon; Xiwei Wu; Brian Armstrong; Nagy Habib; John J. Rossi (Molecular Therapy: Nucleic Acids, 2019)
Human glioblastoma (GBM) is the most aggressive malignancy of the CNS, with less than 5% survival. Despite great efforts to find effective therapeutics, current options remain very limited. To develop a targeted cancer therapeutic, we selected RNA aptamers against platelet-derived growth factor receptor α (PDGFRα), which is a receptor tyrosine kinase. One RNA aptamer (PDR3) with high affinity (0.25 nM) showed PDGFRα specificity and was internalized in U251-MG cells. Following treatment with the PDR3 aptamer, expression of the transcription factor STAT3 (signal transducer and activator of transcription 3) was inhibited, whereas the expression of the histone demethylase JMJD3 and the tumor suppressor p53 were upregulated. PDR3 also upregulated serine phosphorylation of p53, which subsequently mediated apoptosis through the death receptors: tumor necrosis factor (TNF)-related apoptosis-inducing ligand receptors 1/2 (TRAIL-R1/R2), Fas-associated via death domain (FADD), and Fas. PDR3 significantly decreased cell viability in a dose-dependent manner. Furthermore, translocation of PDR3 into the nucleus induced hypomethylation at the promoters of cyclin D2. To assess the feasibility of targeted delivery, we conjugated PDR3 aptamer with STAT3-siRNA for a chimera. The PDR3-siSTAT3 chimera successfully inhibited the expression of target genes and showed significant inhibition of cell viability. In summary, our results show that well-tailored RNA aptamers targeting the PDGFRα-STAT3 axis have the potential to act as anti-cancer therapeutics in GBM. Keywords: PDGFRα aptamer, STAT3, p53, apoptosis, GBM